ALUN â ALUN KOTA YOGYAKARTA MASA KINI Ruang Kota sebagai Wadah Komunikasi Sosial Kota - , RAHADEA BHASWARA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yogyakarta, a city known to maintain its bound on the old tradition. However, we cannot disavow that Yogyakarta still is one of the centers in Indonesian progressive movements. Yogyakarta is the place where conservative â progressive